A mitochondria-localized oxygen self-sufficient two-photon nano-photosensitizer for ferroptosis-boosted photodynamic therapy under hypoxia. (June 2022) - Wei, Fangmian; Karges, Johannes; Shen, Jinchao; Xie, Lina; Xiong, Kai; Zhang, Xiting; Ji, Liangnian; Chao, Hui
Abstract: Photodynamic therapy (PDT) is a medical technique that has received increasing attention over the last years for the treatment of cancer due to its high spatiotemporal selectivity and non-invasive nature. However, its therapeutic potential is strongly limited due to the hypoxic environment found in solid tumors which is hampering the production of therapeutically active species. To overcome this drawback, herein, the functionalization of graphitic carbon nitride nanosheets with mitochondria-targeting iridium(III) polypyridine complexes for oxygen self-sufficient two-photon PDT is reported. The nanomaterial was found to synergistically generate O2 from endogenous H2 O2 and H2 O as well as to produce a mixture of 1 O2, OH, and O2 - therapeutic species, presenting the ability to tackle hypoxic tumor microenvironments and intervene by a multimodal mechanism through combined type I and type II two-photon PDT. Capitalizing on this, the nanosheets demonstrated to cause significant cellular damage under hypoxic conditions towards monolayer cancer cells as well as three-dimensional multicellular tumor spheroids by combined apoptosis and ferroptosis. The nanomaterial showed to eradicate a hypoxic human melanoma cancer tumor inside a mouse model upon two-photon irradiation at 750 nm within a single treatment. To the best of our knowledge, this study presents the first example of iridium complex functionalized graphitic carbon nitride nanosheets as photosensitizers for the treatment of hypoxic tumors upon clinically relevant two-photon irradiation. Graphical Abstract: A mitochondria-localized oxygen self-sufficient two-photon nano-photosensitizer was developed to cause significant cellular damage under hypoxic conditions by combined apoptosis and ferroptosis. ga1 Highlights: A facile coordinative modification of g-C 3 N 4 with Ir(III) complexes was developed. Ir-g-C 3 N 4 is able to sustainably generate O2 from endogenous H2 O2 and H2 O. Ir-g-C 3 N 4 is able to produce multiple types of reactive oxygen species and act as a combined type I and type II PDT agent. Ir-g-C 3 N 4 was found to selectively accumulate in the mitochondria of cancerous cells and induced cell death by combined apoptosis and ferroptosis.